Altered synchronous neural activities in retinal vein occlusion patients: A resting-state fMRI study - Xiao, Yu Mei; Gan, Fan; Liu, Hui; Zhong, Yu Lin (Frontiers in Human Neuroscience, 2022)
Abstract Objective: Retinal vein occlusion (RVO) is the second most common retinal vascular disorder after diabetic retinopathy, which is the main course of vision loss. RVO might lead to macular edema, causing severe vision loss. Previous neuroimaging studies demonstrated that RVO patient were accompanied by cerebral changes and related to stroke. The purpose of the study is to investigate synchronous neural activities changes in the RVO patients. Methods: A total of 50 RVO patients and 48 healthy subjects with matched sex, age and education were enrolled in the study. The ReHo method was applied to investigate synchronous neural activities changes in the RVO patients. Result: Compared with HC, RVO patients showed increased ReHo values in the bilateral cerebelum_4_5. on the contrary, RVO patients had decreased ReHo values in the bilateral middle occipital gyrus, right cerebelum_crus1 and right inferior temporal gyrus. Conclusion: Our study demonstrated that RVO patients were associated with abnormal synchronous neural activities in the cerebelum, middle occipital gyrus and inferior temporal gyrus. These findings shed a new insight into neural mechanisms of vision loss in RVO patients.